Differential tissue deformability underlies fluid pressure-driven shape divergence of the avian embryonic brain and spinal cord - McLaren, Susannah B.P.; Xue, Shi Lei; Ding, Siyuan; Winkel, Alexander K.; Baldwin, Oscar; Dwarakacherla, Shreya; Franze, Kristian; Hannezo, Edouard; Xiong, Fengzhu (Developmental Cell, 2025)
An enlarged brain underlies the complex central nervous system of vertebrates. The dramatic expansion of the brain that diverges its shape from the spinal cord follows neural tube closure during embryonic development. Here, we show that this differential deformation is encoded by a pre-pattern of tissue material properties in chicken embryos. Using magnetic droplets and atomic force microscopy, we demonstrate that the dorsal hindbrain is more fluid than the dorsal spinal cord, resulting in a thinning versus a resisting response to increasing lumen pressure, respectively. The dorsal hindbrain exhibits reduced apical actin and a disorganized laminin matrix consistent with tissue fluidization. Blocking the activity of neural-crest-associated matrix metalloproteinases inhibits hindbrain expansion. Transplanting dorsal hindbrain cells to the spinal cord can locally create an expanded brain-like morphology in some cases. Our findings raise questions in vertebrate head evolution and suggest a general role of mechanical pre-patterning in sculpting epithelial tubes.
CRIS-Team Scopus Importer:2025-05-23
Keywords: brain; development; ECM; extracellular matrix; lumen; morphogenesis; neural tube; pressure; spinal cord; tissue fluidity; tissue mechanics